Perception and knowledge of patients with type 2 diabetes in hospital universiti sains malaysia about their disease and medication: a qualitative study - Norhisham, Nur ‘Aina ‘Aqilah (Universiti Sains Malaysia, 2024)
This study aims to identify and explore perception and knowledge about diabetes and its medication and understand the factors contributing to medication adherence among Type 2 Diabetes Mellitus (T2DM) patients in Hospital USM. A qualitative study was conducted focusing on the factors that affect perception and knowledge of T2DM patients about their disease and medication patients in hospital USM. A total of 20 participants participated in a semi-structured interview session. Recordings from interview sessions were transcribed, and qualitative data was thematically analysed. The result shows that knowledge-related, therapy-related and psychological-related factors are the factors that affect perception and knowledge of T2DM patients about their disease and medication patients in hospital USM. Therefore, dietitians and other related healthcare professionals must develop appropriate intervention to make sure patients can overcome the barriers and increase the motivational factors to improve their perception and knowledge as well as improving medication adherence. Such intervention will help them to improve their health status and quality of life. Further research could be conducted by involving a larger sample of adult patients and different Malaysian demographic group including diversity of ethnicity.